AptaFluorescence: An aptamer-based fluorescent imaging protocol for biomolecule visualization. - Crystal Chia Yin Ling; Melissa Jane Fullwood (PLoS ONE)
Immunofluorescence is highly dependent on antibody-antigen interactions for accurate visualization of proteins and other biomolecules within cells. However, obtaining antibodies with high specificity and affinity for their target proteins can be challenging, especially for targets that are complex or naturally present at low levels. Therefore, we developed AptaFluorescence, a protocol that utilizes fluorescently labeled aptamers for in vitro biomolecule visualization. Aptamers are single-stranded nucleic acid molecules that fold into three-dimensional structures to bind biomolecules with high specificity. AptaFluorescence targeting the c-MYC protein was evaluated in doxycycline-inducible c-MYC U2OS cells. AptaFluorescence signals were more distinct compared to the diffuse immunofluorescence signals. AptaFluorescence also reliably differentiated doxycycline-treated cells from untreated cells. In conclusion, AptaFluorescence is a novel, easy to perform, aptamer-based protocol that will have broad applicability across various biological endeavours for visualizing biomolecules, especially in cases where antibodies with high affinity and specificity for their target proteins are lacking.